An examination of major works for wind band : Firework music by George Frederick Handel arranged by Philip Gordon, Portrait of a clown by Frank Ticheli, A childhood hymn arranged by David Holsinger, and Citadel concert march by Frank Erickson - Rogers, James Delbert (Kansas State University, 2013)
The following report is research and analysis from the comprehensive examination question based on the Graduate Conducting Recital of James D. Rogers. The recital, performed by the Mission Valley High School Band, was held in the gymnasium of Mission Valley Schools USD #330 on May 4, 2013 at 7:00 p.m. Pieces of music performed were Firework Music by George Frederick Handel and arranged by Phillip Gordon, Portrait of a Clown by Frank Ticheli, A Childhood Hymn by David Holsinger, and Citadel: Concert March by Frank Erickson. In addition to the analysis of the mentioned music, this document also contains rehearsal plans used in the preparation of the music for performance.
Keywords: Band; Music; Music (0413)